Nutrient Content of Bioconverted Palm Oil Using Rizhopus olygosporus as Feed - Marwah, Marwah; Hasanuddin, Asriani; Syahrir, Syahrir (FAPETKAN UNTAD, 2021)
The purpose of this study was to determine the nutrient content of the bioconverted palm oil sludge using Rhizopusoligosporus so that it is suitable as functional feed. The used materials were oil palm mud flour and Rhizopusoligosporus fungus. The research design used a factorial completely randomized design with 8 treatments and 3 replications. The treatment consisted of two factors, the first factor was 4 concentrations, namely (0%, 5%, 10% and 15%) and two fermentation times, namely (60 and 96 hours). All treatments were analyzed for nutrient content including dry matter content (BK), crude protein (PK) and crude fiber (SK) fermented palm sludge. The results of the analysis of variety showed that the treatment had a very significant effect (P <0.01) on the content of BK, PK, SK and there was an interaction between the concentration of fungi and fermentation time on SK. The highest dry matter content for BK was obtained in W2K15 treatment (83.24%), PK on W2K15 (18.44%), and SK on W2K15 (24.00%).